Effects of Time Delay on Degree of Conversion of Contemporary Orthodontic Band Adhesives - Bayram Çörekci; Ebubekir Toy; Siddik Malkoc; Bora Ozturk; S. Beniz Gunduz (Turkish Journal of Orthodontics, 2013)

(untitled)
Objective:For prolonged use in the oral cavity, orthodontic band adhesives should have certain physical properties to ensure the best clinical performance. The degree of conversion (DC) of orthodontic band adhesives has been found to affect their mechanical properties. The aim of this study was to investigate the effects of time delay on the DC of orthodontic band adhesives.Materials and Methods:Fourier-transform infrared spectroscopy was used to evaluate the DC of 3 adhesives (Bisco Ortho Band Paste LC, Multi Cure Glass Ionomer Band Cement, Transbond Plus Light Cure Band Adhesive) immediately after they had been polymerized and stored in artificial saliva at 37 ± 1°C for 30 days. Thirty disc-shaped specimens (10 for each adhesive) were fabricated in Teflon molds (6.0 × 1.0 mm). The samples for each adhesive were divided further into 2 groups (n=5).Results:The DC was significantly influenced by the band adhesive type (p < 0.05), and there were significant differences among band adhesive types for the DC after 30 days.Conclusion:The value of the DC could change with time delay.